Influence of Cognitive and Emotional Advertisements on Biosphere Reserve Image and Visitation Intention for Youth - ARKLINA, Anda; GRINBERGA, Kristine; SINGH, Nripendra; LIVINA, Agita (Journal of Environmental Management and Tourism; Vol 11 No 6 (2020): JEMT Volume XI, Issue 6(46) Fall 2020, 2020)
The purpose of this study is to explore the role of the North Vidzeme Biosphere Reserve’s image (functional, symbolic and experiential) in building young visitors’ intentions to visit biosphere reserves. Integrated research methods were used. An online survey was conducted for data collection (n=295), and focus group discussions and observations (three groups - two from Latvia and one from Estonia) were conducted about youth traveling behavior in the North Vidzeme Biosphere Reserve. Descriptive statistics and structural equation modeling were used to analyze data. Findings showed that the North Vidzeme Biosphere Reserve has a weak image in the perception of young people. Most respondents agreed that visiting biosphere reserves relieves stress, helps them to socialize, and allows them to escape from daily routine; additionally, they noted that they would visit protected areas more often if they would see their friends visiting them. Youth 15–19 was more excited, pleasureful, and excited about visiting biosphere reserves, but youth 20–25 was more neutral about it. Both groups agreed that there was a lack of advertisements and visibility of these areas on social media platforms. Research results showed that improving functional, symbolic, and emotional images of the North Vidzeme Biosphere Reserve will have a positive effect on youth visiting and revisiting intentions.